Coherent optical effects in two-dimensional nanostructures with semiconductor quantum dots - Prokhorov Alexei; Volkov Valentyn (EPJ Web of Conferences, 2019)
The effects of quantum coherence arising in an ensemble of semiconductor quantum dots located near the surface of two-dimensional optical materials are considered. The conditions for the realization of strong coupling between surface plasmon-polaritons and quantum dot in proximity to graphene are studied.